2014
DOI: 10.2112/jcoastres-d-13-00173.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Submerged Breakwater on Hydrodynamics and Shoreline Change of the East Beach of Beidaihe, Bohai Bay, China

Abstract: Kuang, C.; He, L.; Gu, J.; Pan, Y.; Zhang, Y.; Yang, Y.; Qiu, R., and Zhang, J., 2014. Effects of submerged breakwater on hydrodynamics and shoreline change of the East Beach of Beidaihe, Bohai Bay, China. Journal of Coastal Research, 30(3), 598-614. Coconut Creek (Florida), ISSN 0749-0208.The beaches in Beidaihe of Bohai Bay of China have been eroded since 1950s, clearly evidenced by sand coarsening, rock outcropping, and slope steepening. Beach nourishment is a common coastal management strategy used to prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…To avoid that and simplify calculation, we assume the enrockment only dissipates wave energy but does not affect tidal currents. This assumption can be justified by Kuang et al (2014) and Wen and Liu (2015), which have shown that the construction of low breakwaters does not significantly change the surrounding current field. In our model, waves with large wave height are dampened on reaching the enrockment owing to the limited water depth, while tidal currents go through directly as if the enrockment did not exist there.…”
Section: Simulations Of Upper-flat Enclosure and Lower-flat Enrockmentmentioning
confidence: 97%
“…To avoid that and simplify calculation, we assume the enrockment only dissipates wave energy but does not affect tidal currents. This assumption can be justified by Kuang et al (2014) and Wen and Liu (2015), which have shown that the construction of low breakwaters does not significantly change the surrounding current field. In our model, waves with large wave height are dampened on reaching the enrockment owing to the limited water depth, while tidal currents go through directly as if the enrockment did not exist there.…”
Section: Simulations Of Upper-flat Enclosure and Lower-flat Enrockmentmentioning
confidence: 97%
“…Nearly 45% of the beaches in Qinhuangdao, approximately 80 km long, are not up to the standard of tourism due to shortened beach width, steepened slope, and coarser sand arising from chronic erosion. To tackle the erosion, the local government implemented a series of beach nourishment projects [37,[49][50][51][52] together with submerged breakwaters, artificial headlands, submerged sandbars. However, too many coastal protection structures that calm the hydrodynamic environment too much may cause water quality degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The present measures against the scour can be mainly divided into two sections according to their principles: enhancing the stability of the erodible bed and modifying the flow structure. The former mainly includes toe protection [11], revetments [12, 13] and mattresses [14], while the latter includes groins [15, 16] and submerged breakwaters [17, 18]. However, many of the measures consolidating the stability of sediment on river bed and banks, like the revetments and mattresses, would lead to some environmental and ecological problems.…”
Section: Introductionmentioning
confidence: 99%